Antagonistic activity of recombinant Lactococcus lactis NZ1330 on the adhesion properties of Escherichia coli causing urinary tract infection. (August 2019) - Vasiee, Alireza; Mortazavi, Seyed Ali; Sankian, Mojtaba; Yazdi, Farideh Tabatabaee; Mahmoudi, Mahmoud; Shahidi, Fakhri
Abstract: Death from infectious diseases has caused concerns about increases in the resistance of pathogens, impelling researchers to create novel therapeutic solutions. The management of intestinal tract problems has been the advance use of probiotics in medicine. The aim of this study was evaluate the physicochemical cell surface and adhesion properties of recombinant Lacotococcus lactis NZ1330 containing Ama r 2 gene, followed by the assessment of the antagonistic activity of this strain against the Escherichia coli causing urinary tract infection (UTI) in humans. For this purpose, cloning and expression of Ama r 2 gene were done. Afterwards, acid and bile resistance, which are the primary characteristics of any probiotic, were evaluated. The r- L. lactis NZ1330 was examined for the physicochemical properties of cell surfaces and the adhesion properties against Escherichia coli . Furthermore, the potential of the recombinant strain to adhere to adenocarcinoma intestinal cell line, Caco-2 cells, as well as the antagonistic properties of r- L. lactis NZ1330 against E. coli was investigated. r- L. lactis NZ1330 was capable of surviving at low pH and different concentrations of bile salts. 40.1% hydrophobicity, 36.5% auto-aggregation and 14.4% co-aggregation were observed for this strain. The adhesion level of r- L. lactis NZ1330 was 5.7% which was also confirmed by scanning electron microscopy (SEM). r- L. lactis NZ1330 was able to compete, inhibit and displace the adhesion of Escherichia coli to Caco-2 cells. r- L. lactis NZ1330 was considered to be a reliable probiotic alternative by showing these desirable properties. Results revealed that Ama r 2 gene expression had no effect on the positive probiotic properties of L. lactis NZ1330, proving this strain could be a suitable probiotic host for the expression of this allergen. Highlights: Probiotic properties of recombinant Lactococcus lactis NZ1330 were evaluated. Our results showed there is a good adaptation between r- Lactococcus lactis NZ1330 and gastrointestinal conditions. The antagonistic activity of r- Lactococcus lactis NZ1330 against Escherichia coli causing infection was acceptable.